The Narratives of Female Models toward Sexuality Body (Narrative Analysis of Female Models in Men's Magazine) - Kilau Riksaning Ayu; Triyono Lukmantoro, S.Sos, M.Si (Interaksi Online, 2016)
Body of female models in men's magazine is consumed and perceived as an object in its literal meaning is the recipient of the action. However, the issues are not just about the body's sexuality and about sex, but women also see themselves as subjects that define and determine the direction of the body as the main actor in the decision maker. This research aims to look at the narratives of female models toward sexuality body. The theories used in this research are Beauty Myth, Disciplining the Body and Postfeminism Theory. Furthermore, method used in the research is the analysis of narrative data formulated by Labov and Waletzky. The results of this research in the components of the narrative structure produces several things, are: (1) The form of decision making such as choosing a job as models and appear in men's magazine shows the position of female models as the autonomous subject. (2) The practice of objectifications experienced by female models in the form of negative comments, unpleasant treatment during a photo shoot, became the object of male gaze in men's magazines and became the object of commodification. (3) Female models experienced disciplinary body through standards and job qualifications as model which is influenced by mass media discourses. (4) Female models have autonomy over their body to steer and control the body indicated by the actions taken to prevent and confront various forms of objectification The conclusion of this research is there is a duality position from the narrative of research subject toward sexuality body. First, as an object that experienced practice of objectification through negative comments, unpleasant treatment at a photo shoot session, become an object of male gaze and commodification. Second, the research subjects who worked as a model is an actor of commodification that consciously make choices and do an effort to perform ideal look which is then used to receive various benefits. Appeared in men's magazine is also used to get another jobs that can bring benefit.